(untitled) (Itinera, 2017)
Disgust and fear are very similar. Both seem to be a reaction of defense. The very sense of fear is nonetheless clear enough, that of disgust is not. Fear defends a person from something dangerous; disgust defends a person too, but the danger (if there is) that elicits it is absolutely obscure. In this paper, I will try to clarify in what consists the function of disgust and provide a criterion to identify its object. Basing my analysis on those carried out by Aurel Kolnai and Jean-Paul Sartre, I will claim that fear concerns the very existence of a person, while disgust its very value.Â